2016
DOI: 10.18632/oncotarget.11988
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine induces apoptosis and reduces bortezomib resistance by inhibiting STAT3 in multiple myeloma cells

Abstract: Effective new therapies are urgently needed for the treatment of multiple myeloma (MM), an incurable hematological malignancy. In this study, we evaluated the effects of piperlongumine on MM cell proliferation both in vivo and in vitro. Piperlongumine inhibited the proliferation of MM cells by inducing cell apoptosis and blocking osteoclastogenesis. Notably, piperlongumine also reduced bortezomib resistance in MM cells. In a disseminated MM mouse model, piperlongumine prolonged the survival of tumor-bearing mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…STAT3 inhibition stunts tumour growth by inducing cell apoptosis in many types of malignant tumours [ 19 , 20 ]. OS cell apoptosis was examined to investigate the mechanism underlying the effects of the STAT3 siRNA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…STAT3 inhibition stunts tumour growth by inducing cell apoptosis in many types of malignant tumours [ 19 , 20 ]. OS cell apoptosis was examined to investigate the mechanism underlying the effects of the STAT3 siRNA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Later, the anticancer potential of piplartine and its analogs, alone or in combination, including combination with paclitaxel, cisplatin, gemcitabine and curcumin, have been extensively explored [ 10 , 16 , 19 21 ]. These studies reported the ability of piplartine to induce apoptosis and/or autophagy through modulation of the PI3K/Akt/mTOR, NF-κB, JAK1,2/STAT3 and/or JNK pathways in cancer cells [ 14 , 15 , 22 24 ]. In addition, piplartine is a direct TrxR1 inhibitor and can inhibit cell migration/invasion via ROS/ER/MAPKs/CHOP axis [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 has been reported to be constitutively active in MM patients [ 22 , 54 , 55 ]. Pharmacological agents such as curcumin, piperlongumine, icaritin and LLL12 which blocked STAT3 phosphorylation were reported to suppress primary MM cell viability and/or MM tumor growth in animal models [ 22 , 56 , 57 , 58 ]. Clinically, a high pSTAT3 level has been reported to correlate with poorer progress-free survival and overall survival in newly diagnosed MM patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%